2019
DOI: 10.3389/fphys.2019.01448
|View full text |Cite
|
Sign up to set email alerts
|

Performance Changes Following Heat Acclimation and the Factors That Influence These Changes: Meta-Analysis and Meta-Regression

Abstract: Heat acclimation (HA) is the process of intentional and consistent exercise in the heat that results in positive physiological adaptations, which can improve exercise performance both in the heat and thermoneutral conditions. Previous research has indicated the many performance benefits of HA, however, a meta-analysis examining the magnitude of different types of performance improvement is absent. Additionally, there are several methodological discrepancies in the literature that could lead to increased variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 61 publications
5
28
0
Order By: Relevance
“…The increase in V̇O2max following HA is not a universal observation. Our data agree with a recently published meta‐analysis with 23 studies which reported a small but significant effect of HA on V̇O2max (Hedge's g = 0.30) measured in a temperate environment (Benjamin et al., 2019). The inhomogeneous effect of HA in increasing V̇O2max may be due to the differences in protocols, including exercise mode (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in V̇O2max following HA is not a universal observation. Our data agree with a recently published meta‐analysis with 23 studies which reported a small but significant effect of HA on V̇O2max (Hedge's g = 0.30) measured in a temperate environment (Benjamin et al., 2019). The inhomogeneous effect of HA in increasing V̇O2max may be due to the differences in protocols, including exercise mode (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…C-I-C-IV, mitochondrial complexes I-IV; CaMK, Ca 2+ /calmodulin-dependent protein kinase; COX-4, cytochrome c oxidase subunit 4; Hsp72, heat shock protein 72; PGC-1α, peroxisome proliferator-activated receptor γ coactivator 1α; TFAM, mitochondrial transcription factor A following HA is not a universal observation. Our data agree with a recently published meta-analysis with 23 studies which reported a small but significant effect of HA onV O 2 max (Hedge's g = 0.30) measured in a temperate environment (Benjamin et al, 2019 or approximately 5%) in a temperate environment using trained cyclists . Recently, Waldron et al (2019) Figure 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous findings in male soccer players (Buchheit et al, 2011(Buchheit et al, , 2013(Buchheit et al, , 2016Racinais et al, 2012) show that heat acclimatization can lead to an increase in PV and were corroborated in elite female soccer athletes in the current study, although the PV change failed to reach significance (Figure 4). Laboratory studies utilizing controlled hyperthermia acclimation protocols have reported PV increases of 4-15%, improving cardiovascular stability via maintenance of cardiac output and reductions in HRex, leading to performance enhancement (Chalmers et al, 2014;Periard et al, 2015Periard et al, , 2016Racinais et al, 2015;Casadio et al, 2017;Benjamin et al, 2019;Pryor et al, 2019). While laboratory HA protocols are more controlled, they are less practical and potentially less effective than field-based HA, which has been shown to induce better peripheral adaptations from sport-specific training and better maintenance of skills (Pryor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated training exposures in a hot environment have the potential to induce positive physiological adaptations that can attenuate the negative effects of heat stress by regulating cardiovascular strain while enhancing thermoregulation [e.g., increased plasma volumes (PV) and sweat rates] (Racinais et al, 2015 ). While isothermically controlled, lab-based heat acclimation protocols have demonstrated improvements in both team and endurance sport performance (Pethick et al, 2018 ; Benjamin et al, 2019 ), the resources required to execute an effective acclimation protocol can be expensive (core temperature monitoring), involve extensive equipment (heat chamber), and usually involve non-soccer-specific training (typically cycling) (Buchheit et al, 2011 ; Racinais et al, 2012 ; Chalmers et al, 2014 ). Therefore, the implementation of a field-based, sport-specific heat acclimatization protocol is more ecologically valid and practical for soccer players, while also minimizing time away from training often required for lab-based protocols.…”
Section: Introductionmentioning
confidence: 99%